Kinerja Aparatur Dinas Kependudukan dan Pencatatan Sipil Kota Bandung Dalam Pelayanan Akta Kelahiran Keliling (Suatu Kajian Pada Kualitas Layanan dan Responsibilitas Aparatur) - Tatik Rohmawati; Novi Anna Maria Kope (Jurnal Transformasi Administrasi, 2017)
The mobile service of birth certificate is a new service which is done by the Population and Civil Registration Agency. Instead, this service is still non optimal because of long service and nontransparent services shown by the Population and Civil Registration Agency of Bandung. The theory used in this research can be seen from the aspect of performance evaluation, which are quality services and responsibilities. This theory is based on Agus Dwiyanto. This research used descriptive method with qualitative approach. Then, the techniques used in collecting data in this research were literature studies, field studies and observation, and also interview. The informant of this research were apparatus of the Population and Civil Registration Agency of Bandung who give mobile service of the birth certificate. The purposive and accidental techniques were used to determine the informant. Based on the result of the research, apparatus performances of Population and Civil Registration Agency of Bandung who give mobile service of the birth certificate is good. Then, the creating process of the birth certificate runs well enough. Those can be seen from the quality services and well-guaranteed responsibilities. The apparatus attitude in working is normative. The public response show that the apparatus of the Population and Civil Registration Agency of Bandung work well enough.